Electronic energy meter management system (EEMMS) - Makonza, Evidence (Midlands State University, 2019)
The core aspect behind developing Electronic Energy Meter Management System (EEMMS) was a result of inefficiency of the manual system that was used at the organization. The main aim was to develop a computerized system that will curb the problems currently encountered by using the existing manual system by integrating information systems process. The instruments which were used to come up with the system include MySQL database, Adobe Dreamweaver CS6, SMTP email service and Apache server. Various feasibility studies were carried out to identify if it is worthy to build the new system. Feasibility studies has shown that the available hardware and software can be used with the new system without facing any challenges and that the benefits of the new system outweigh its costs. Information gathering methodologies were used to identify how the old system works. These include interviews, questionnaires and observations. The system was designed by making much emphasis on the architectural, physical, database and logical design. The system was tested using various testing techniques which encompasses black box and white box testing. Validation and verification processes were carried out and proved that the system meets that expected standards. The system was installed using the parallel run conversion method. The system needs to be maintained for it to provide best results. The users of the system are recommended to stick to the basics learnt during the training, and should they face any problems, they should consult the system administrator.